A life cycle labour supply model with taxes estimated on German panel data: the case of parallel preferences - Laisney, Francois; Lechner, Michael; Van Soest, Arthur; Wagenhals, Gerhard (Economic & Social Studies, 1993)
We estimate Frisch labour supply functions for married women using information on desired hours, under the assumptions that these are based on a smooth convex approximation of the budget constraint. The minimum distance approach used allows for correlated random effects both in the wage and in the taste-shifter equations, and for an unbalanced panel. We use a subsample of the German Socio-economic Panel for the years 1985-1989.
Keywords: Labour supply; Taxation; Life cycle; Germany